Pengetahuan Masyarakat di Kota Samarinda tentang Teknologi Informasi - Faldi Faldi; Bambang Setiaji; Rahman Anshari; Rizky Kurniawan Syamat; Hasyrul Hamzah; Widya Rahmah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Human curiosity about something will always increase the level of knowledge because everything known is knowledge. Such is knowledge, along with the times, information technology has become one of the influential factors in business success because of its advantages in facilitating work in everyday life. Everything related to the process, implementation as a tool, manipulation, and information management is a function of information technology. Without the help of information technology in the business world, it can make the promotion of a product less competitive with other competitors, weaken marketing management, worsen the company's infrastructure, and experience difficulties in running the business. This activity aims to see the level of public knowledge related to information technology, which is very helpful in daily life. This service uses a descriptive survey method associated with the level of general knowledge about information technology with a measuring instrument in the form of a questionnaire distributed to the public through webinar activities with random sampling so that 290 respondents are obtained consisting of students, private workers, and so on. Based on the results, it is known that as many as 73.6% of respondents have understood how to apply information technology. As many as 60% of respondents stated that information technology is fundamental in everyday life because it can facilitate all existing work. Most people in Samarinda already know how to apply and the importance of this information technology in promoting their work.